Centralization of Power and Development of the American Federal System. 1789-1979 - Scheiber, Harry N. (Czasopismo Prawno-Historyczne, 1980)
The American federal system was not created by the framers of the 1787 Constitution to accommodate as citizens in one nation, federally organized, the culturally distinctive elements of the North American population. The American Indian nations were recognized as sovereign — as the subject of treaty powers — in the 1787 Constitution; and the black slave population was treated as property only, albeit property of a sort that affected representation in the national Congress. Rather than being a federal system designed to afford expression to such distinctive cultural interests, territorially based or otherwise, within the nation, the Constitution was a document for the organization of power affecting the white, Euro-American population as it had already organized its government in thirteen states with individual constitutional and political identities dating from the original charters under the British colonial and imperial system. To be sure, the thirteen constituent states had some distinctive interests; above all, there was the division between the plantation-agriculture, slave-owning states and the New England and Middle Atlantic states in which agriculture was not plantation-based and slave ownership was minimal. For purposes of comparison with numerous other federal states, either of the 19th century or the contemporary world, the United States did not face the intractable problems of giving political expression and assuring elements of autonomy to authentically distinctive cultural or ethnic subgroups. (It is, of course, one of the ironies of U.S. history that from origins thus free of the invariably difficult problem of accommodating pluralism, the nation was plunged into a bloody Civil War 70 years later).